Traction Converter Development of Hybrid-power Diesel Locomotive - RAO Pei-nan; CHAI Duo; ZHANG Yi (机车电传动)
Performance and main technic parameters of hybrid-power diesel locomotive traction converters were introduced,which overcame shortages of traditional diesel locomotive by using both power battery and diesel generator for traction.Operating principle,development process,main characteristics and innovation of traction converters were described particularly.